Benjamin’s “Afterlife”: A Productive (?) Mistranslation In Memoriam Daniel Simeoni - Disler, Caroline (TTR, 2011)
The concept of “afterlife” constitutes a central theme in Die Aufgabe des Übersetzers, yet the German equivalent to “afterlife” does not appear once in Walter Benjamin’s seminal essay on translation. This article investigates the German term that Benjamin has in fact chosen and examines the highly problematic translation of his idea. Some of the resulting interpretations by translation theorists are presented, along with the potentially deleterious effects on the translation community.